Elaboration and characterization of cheese analogous to Boursin with functional characteristics (Research, Society and Development, 2020)
Boursin cheese is a little-known cheese in Brazil, but in France, it is a commercial type of triple-cream cheese made from goat's milk. The aim of this study was to develop a cheese similar to Boursin from bovine milk with functional characteristics, adding flaxseed (Linum usitatissimum) as a prebiotic component, and kefir as a probiotic component, and to determine quantitatively through physical analysis. chemical constituents. The treatments were arranged as follows, Treatment 1 (T1) - standard, Treatment 2 (T2) received only the probiotic, Treatment 3 (T3) only the prebiotic, and Treatment 4 (T4) received both the prebiotic and probiotic. Statistical analysis was performed using the Tukey test to evaluate the physical-chemical parameters determined for pH, titratable acidity, lipids, proteins, total soluble solids and ashes). The results show that the Boursin cheese treatments did not differ significantly by the Tukey test in terms of protein, lipids, total soluble solids and pH; however, they differed in terms of lactic acid, flaxseed, ash and for samples with kefir.